RETRACTED: Dysregulation of Survivin-Targeting microRNAs in Autoimmune Diseases: New Perspectives for Novel Therapies - Shomali, Navid; Suliman Maashi, Marwah; Baradaran, Behzad; Daei Sorkhabi, Amin; Sarkesh, Aila; Mohammadi, Hamed; Hemmatzadeh, Maryam; Marofi, Faroogh; Sandoghchian Shotorbani, Siamak; Jarahian, Mostafa (Frontiers in Immunology, 2022)
It has been well established that the etiopathogenesis of diverse autoimmune diseases is rooted in the autoreactive immune cells' excessively proliferative state and impaired apoptotic machinery. Survivin is an anti-apoptotic and mitotic factor that has sparked a considerable research interest in this field. Survivin overexpression has been shown to contribute significantly to the development of autoimmune diseases via autoreactive immune cell overproliferation and apoptotic dysregulation. Several microRNAs (miRNAs/miRs) have been discovered as being involved in survivin regulation, rendering the survivin-miRNA axis a perspective target for autoimmune disease therapy. In this review, we discuss the role of survivin as an immune regulator and a highly implicated protein in the pathogenesis of the autoimmune disease, the significance of survivin-targeting miRNAs in autoimmunity, and the feasibility of targeting the survivin-miRNA axis as a promising therapeutic option for autoimmune diseases.